2020
DOI: 10.1039/d0lc00302f
|View full text |Cite
|
Sign up to set email alerts
|

Direct loading of blood for plasma separation and diagnostic assays on a digital microfluidic device

Abstract: The integration of 3D porous membranes in a digital microfluidic device enables the generation of cell-free plasma from finger-stick volumes of blood with in-line, on-chip analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…This membrane was chosen for its low nonspecific binding characteristics, hydrophilic nature, and asymmetric design, which enabled sufficient (μL) separation volumes. 13,23,24 The filtered sample passively flowed into the capture region of the microfluidic device. Here, the sample was mixed with functionalized magnetic beads to capture target biomarkers (Fig.…”
Section: Sample-to-answer Workflowmentioning
confidence: 99%
See 1 more Smart Citation
“…This membrane was chosen for its low nonspecific binding characteristics, hydrophilic nature, and asymmetric design, which enabled sufficient (μL) separation volumes. 13,23,24 The filtered sample passively flowed into the capture region of the microfluidic device. Here, the sample was mixed with functionalized magnetic beads to capture target biomarkers (Fig.…”
Section: Sample-to-answer Workflowmentioning
confidence: 99%
“…hospitals, bedside) have grown in popularity as promising alternatives to central laboratories for a variety of analytes due to their low-cost, low-complexity, and analytical capabilities. 6,8,[13][14][15][16] Advances in these PoC systems have shown expedited assay times (minutes), expanded testing locations (portability), and reduced sample volume needs (μLs). Moreover, these systems maintain clinically relevant limit of detections (LoDs), limit of quantifications (LoQs), dynamic ranges, testing linearity, and analytical sensitivities and specificities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cell lysis, such as hemolysis and leukolysis, should be avoided as DNA or RNA released from lysed cells may interfere with circulating cell-free DNA and RNA levels, resulting in erroneous readings, particularly in the case of liquid biopsy assays. In recent years, there has been a growing interest in micro-scale blood plasma separation (BPS) both as a replacement for traditional centrifugation and as preliminary modules to complete Lab-On-Chip devices [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The component concentrations in the plasma separated by those microfluidic devices have rarely been analyzed. It has been shown that the microstructures and surface properties of microfluidic devices can interact with the components in the plasma, which can lead to the component concentrations in the separated plasma being inconsistent with those of the “gold standard” of the centrifuge method [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%